Sistema web de ajuda ao servidor público: um produto construído através da ciência de dados aplicada a dados abertos da remuneração dos servidores públicos - Souza, Maison Marcel Madri Galvão dos Santos (Brasil, 2024)
This study introduces a solution to enhance the presentation of open data on transparency platforms, specifically focusing on public servants' remuneration. The research aims to develop a web-based system tailored to simplify data queries, providing users with comprehensive analyses, rankings, and filtering options. Employing advanced data science techniques, the study transforms raw data into actionable insights. Primary data sources are sourced from open datasets from both Federal and State Executive branches, accessed via an Application Programming Interface (API). Through a case study approach, two distinct analyses were conducted: one centered on federal servants and another concerning the State of Amazonas' public servant data. Technically, the system leverages cutting-edge technologies such as Vue.js, Firebase, and Tailwind CSS, all hosted on the cloud through Amazon Amplify services. The outcome is a robust web platform offering enhanced functionalities compared to current transparency portals.